Analisis Miskonsepsi Nilai π pada Materi Lingkaran dalam Buku Senang Belajar Matematika: Antara Nilai Sebenarnya dan Realitas Irasional - Syifa Eriza Nasution; Joyce Lidya Patricia Daeli; Pujiono Sihite; Marcelly Claudia Sagala; Immanuel Simbolon; Wingston Leonard Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Understanding mathematical concepts is inseparable from the clarity of their definitions and presentation in textbooks. One fundamental concept that frequently appears in school curricula, from elementary, middle, and high school levels, is the constant π (phi) in the topic of circles. Mathematically, π is an irrational number obtained from the ratio of a circle's circumference to its diameter. However, in practical learning, the value of π is often simplified to or 3.14. This practical presentation has the potential to lead to misconceptions in students, namely, that they assume π is a rational number. This study used qualitative methods with document analysis techniques in the